The history of translations of R. Burns’s lyrics into the Russian language (Eurasian Journal of Philology Science and Education, 2018)
The article is devoted to the study of the history and theoretical principles of translation of the poetry of R. Burns into Russian. As the comparative analysis has shown, translations can contain conditional changes in comparison with the original and these changes are absolutely necessary and justified, if the goal is to create a similar unity of form and content on the material of another language, however the same analysis confirms that the equivalence of the translation depends both on volume, and on the nature of these changes. The article explores the main types and principles of translations, which translators resort to when recreating the work of R. Burns in Russian during the XIX-XX centuries.